2015
DOI: 10.1152/ajprenal.00296.2015
|View full text |Cite
|
Sign up to set email alerts
|

The ugly duckling of urinary acidification: what is the contribution of the thick ascending limb of the loop of Henle to urinary acidification?

Abstract: THE KIDNEY EXCRETES ACID in the form of titratable acidity and ammonium as well as in the form of free protons. The latter causes urinary acidification together with the reabsorption of filtered bicarbonate. Inborn or acquired forms of renal tubular acidosis (RTA) reduce the capacity of the kidneys to form ammonium and excrete acids (9). According to the functional defect and predominant site of renal damage, different subtypes of RTA have been classified: type I or distal RTA (dRTA), describing defects locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We recently showed that urine acidification by furosemide occurs to a large part independently of ENaC . Importantly, we demonstrated that furosemide directly stimulates pronounced H + secretion in the thick ascending limb (TAL) via the apical Na + /H + exchanger NHE3, which could be inhibited by a specific NHE3 inhibitor . These results substantially challenge the “voltage hypothesis” and triggered our motivation to further investigate the mechanism underlying diuretic‐induced urinary acidification.…”
Section: Introductionmentioning
confidence: 93%
“…We recently showed that urine acidification by furosemide occurs to a large part independently of ENaC . Importantly, we demonstrated that furosemide directly stimulates pronounced H + secretion in the thick ascending limb (TAL) via the apical Na + /H + exchanger NHE3, which could be inhibited by a specific NHE3 inhibitor . These results substantially challenge the “voltage hypothesis” and triggered our motivation to further investigate the mechanism underlying diuretic‐induced urinary acidification.…”
Section: Introductionmentioning
confidence: 93%